2004
DOI: 10.1126/science.1096096
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the Tyrosine Phosphatome in Colorectal Cancers

Abstract: Tyrosine phosphorylation, regulated by protein tyrosine phosphatases (PTPs) and kinases (PTKs), is important in signaling pathways underlying tumorigenesis. A mutational analysis of the tyrosine phosphatase gene superfamily in human cancers identified 83 somatic mutations in six PTPs (PTPRF, PTPRG, PTPRT, PTPN3, PTPN13, PTPN14), affecting 26% of colorectal cancers and a smaller fraction of lung, breast, and gastric cancers. Fifteen mutations were nonsense, frameshift, or splice-site alterations predicted to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
478
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 481 publications
(498 citation statements)
references
References 27 publications
18
478
1
1
Order By: Relevance
“…Both genes are considered tumor suppressors. 34,35 The 6q duplication that case II.7 inherited from his mother is located nearby (97 kb downstream) a locus (TULP4) associated with height. 1 One of the duplicated genes (ENPP2) in case II.8 encodes for a lysophospholipase D, producing lysophosphatidic acid inducing cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Both genes are considered tumor suppressors. 34,35 The 6q duplication that case II.7 inherited from his mother is located nearby (97 kb downstream) a locus (TULP4) associated with height. 1 One of the duplicated genes (ENPP2) in case II.8 encodes for a lysophospholipase D, producing lysophosphatidic acid inducing cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in a recent study, PTPN3 was identified as 1 of 6 PTPs of all 87 that are encoded in the human genome to be frequently mutated in colorectal cancer cell lines (36). Interestingly, of the other 5 PTPs, 1, PTPL1/FAP-1 (PTPN13), also contains FERM and PDZ domains and another, PTP36/PEZ (PTPN14), contains a FERM domain.…”
Section: Discussionmentioning
confidence: 99%
“…For example, kinome sequencing has involved sequencing the coding regions of several hundred kinase genes, such as the tyrosine kinases. This approach has led to the discovery of mutations in several kinase genes including tyrosine kinase, tyrosine phosphatase and lipid kinase genes in colorectal cancer [109][110][111][112] . Similarly, sequencing known components of an important signaling pathway led to the identification of BRAF mutations in melanomas 113 .…”
Section: Genetics Markersmentioning
confidence: 99%